MEDIA PEMBELAJARAN PENDIDIKAN JASMANI ADAPTIF TERHADAP PERKEMBANGAN SENSORIK DAN MOTORIK SISWA SLB - Yovi Alia yovi; Meirizal Usra; Soleh Solahuddin (JURNAL ILMU KEOLAHRAGAAN, 2026)
This study aims to analyze the use of Pick A Sport and Color Jump learning media in improving the sensory and motor development of children with special needs (ABK) in Special Needs Schools (SLB). The method used is a Systematic Literature Review (SLR) with the PRISMA approach to select articles systematically and objectively. The literature search was conducted through the Google Scholar, Lens.org, and ScienceDirect databases with publication criteria for 2020–2025. The selection results obtained nine articles relevant to the research focus. The study findings indicate that Pick A Sport and Color Jump media are effective in providing multisensory stimulation including visual, tactile, and body movement, thereby improving gross motor skills, coordination, balance, and sensory responses of children with special needs. This media also increases motivation, active participation, and student learning interest during learning. Thus, the use of Pick A Sport and Color Jump media can be an alternative innovative learning media that supports the sensory and motor development of children with special needs in SLB. Keywords: Children with Special Needs, Learning Media, Pick A Sport, Color Jump, Sensory Motor Development